Predictors of a Variceal Source among Patients Presenting with Upper Gastrointestinal Bleeding - Ahmad Alharbi; Majid Almadi; Alan Barkun; Myriam Martel; The REASON Investigators (Canadian Journal of Gastroenterology)
BACKGROUND: Patients with upper gastrointestinal bleeding (UGIB) require an early, tailored approach best guided by knowledge of the bleeding lesion, especially a variceal versus a nonvariceal source.